LANGUAGE AND COMMUNITY RESPONSE ON THE APPEAL AND ANNOUNCEMENT OF COVID-19 - Ladyanna, Sonezza; Almos, Rona; Merina, Yola (TELL - US JOURNAL, 2020)
Language in appeals and announcements regarding Covid19 in public spaces is an important factor in communication regarding the handling of this pandemic. In this regard, this article describes the language and reactions of the public to the appeals and announcements regarding Covid19. The data source in this study is the language of appeals and announcements regarding Covid19 in public spaces in West Sumatra Province, Indonesia. The data in this study are linguistic variations and people's responses to linguistic variations in the Covid19 appeal and announcement. Data collection was carried out through observation and questionnaires. The analysis was carried out in the framework of sociolinguistic study. Based on the results of the analysis, it can be concluded that the languages used are Indonesian with formal and informal varieties, English, and Minangkabau language, also found the use of abbreviations, acronyms, and mixing-code. People have different reactions regarding the use of the language, some agree and disagree, on the other hand there are those who are affected and not. This difference is influenced by age and education. The novelty in this research is the finding that appeals and announcements relating to handling Covid19 will be more optimal if they are equipped with the number of victims of this virus.